Efecto de la aplicación de chlorella spp. y un consorcio de rizobacterias en el crecimiento, desarrollo y rendimiento agrícola de brassica oleracea var. italica - Alvarado Romero, Freddy Alexander (2021)
The application of algae and rhizobacteria is intended to elucidate the beneficial effect of these microorganisms on broccoli cultivation, as well as to reduce production costs and the environmental impact associated with chemical fertilization. The research was conducted in the San José neighborhood, Sucre parish in the city of Loja, with the objective of evaluating the effect of the application of Chlorella spp. and a consortium of rhizobacteria on the growth and agricultural yield of Brassica oleracea var. Italica. A completely randomized block design (CSBD) was used, with six treatments and four replicates. For the economic analysis, the methodology of the International Maize and Wheat Improvement Center (CIMMYT) was used. The results indicated that the application of rhizobacteria, Chlorella spp., organic matter and chemical fertilizers did not influence plant height and number of leaves. Treatment 6 (chemical fertilizer) significantly influenced plant diameter, weight and yield with a total of 13. 40 cm, 291. 5 g and 16. 70 t ha-1, followed by treatments 3 (Chlorella spp., with 13. 20 cm, 287. 8 g and 16. 40 t ha-1) and 2 (Chlorella spp. and rhizobacteria consortium, with 13. 10 cm, 282. 8 g and 16. 20 t ha-1). The application of Chlorella spp. and rhizobacteria consortium optimized the content of: P, K, Fe, Ca, Mg, S, B, MO and improved electrical conductivity and soil texture. The best benefit/cost ratio (B/C) per hectare was presented by treatment 3 with 4.66 USD, while treatment 6 presented the lowest B/C with 2.9 USD Key words: Brassica oleracea var. Italica, Chlorella spp, rhizobacterial consortium, development, yield.